2021
DOI: 10.21203/rs.3.rs-257946/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cervical Cancer Screening Uptake and Determinant Factors Among Women in Ambo Town, Western Oromia, Ethiopia: Community based Cross Sectional Study

Abstract: Background: Cervical cancer is one of the principal causes of cancer death among women worldwide. It is the second most common cancer and the leading cause of cancer-related death in Ethiopian women; about 77.6% of women died of 6,294 new cases reported in 2019. Early screening for cervical cancer has substantial advantage to reduce the incidence, morbidity, and mortality attributed to cervical cancer. So far, there are limited evidence on the level of cervical cancer screening uptake and its determinant in lo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…We learned that there were certain differences in depression and anxiety before and after the intervention, but the degree of depression and anxiety in the experimental group was significantly greater than that in the control group. Therefore, this study puts forward the following suggestions for the next step of case management nursing practice: ① case management nurses should pay more attention to patients' mental health and rehabilitation needs, encourage patients to express their inner feelings, and solve patients' problems in time by coordinating various relationships [15,16]. ② In the practice of case management, case management nurses should not only teach their family members disease-related knowledge and skills but also pay attention to communication with their family members, fully understand their physical and mental needs, and provide targeted psychological and social support [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…We learned that there were certain differences in depression and anxiety before and after the intervention, but the degree of depression and anxiety in the experimental group was significantly greater than that in the control group. Therefore, this study puts forward the following suggestions for the next step of case management nursing practice: ① case management nurses should pay more attention to patients' mental health and rehabilitation needs, encourage patients to express their inner feelings, and solve patients' problems in time by coordinating various relationships [15,16]. ② In the practice of case management, case management nurses should not only teach their family members disease-related knowledge and skills but also pay attention to communication with their family members, fully understand their physical and mental needs, and provide targeted psychological and social support [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The participants thought that they were not susceptible to cervical cancer disease and that the screening service was not necessary. A similar nding from Wolaita zone showed that women did not need to go to health institution for take of health care unless they have sign, symptoms and complication of the disease (12) and Ambo town (14). The investigators found that a woman's who had accepted cervical cancer screening service mostly had after the disease was complicated.…”
Section: Discussionmentioning
confidence: 99%